2011
DOI: 10.1016/j.jcrs.2011.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of cataract surgery in eyes with a low corneal endothelial cell density

Abstract: The results suggest that modern techniques for cataract surgery provide excellent visual rehabilitation in many patients with a low preoperative ECD. Shorter AL, diabetes mellitus, and posterior capsule rupture were risk factors for greater ECD loss and bullous keratopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 34 publications
2
61
0
Order By: Relevance
“…They assumed that their soft-shell technique (instillation of two different viscoelastic materials) combined with the phaco chop technique was the reason for reduced endothelial cell damage. Several studies found a higher ECL in patients with Type 2 diabetes mellitus [17,35,18].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…They assumed that their soft-shell technique (instillation of two different viscoelastic materials) combined with the phaco chop technique was the reason for reduced endothelial cell damage. Several studies found a higher ECL in patients with Type 2 diabetes mellitus [17,35,18].…”
Section: Discussionmentioning
confidence: 98%
“…Studies found a shorter AL (<23.0 mm) and diabetes mellitus to be a risk factor of endothelial cell loss [18,17]. In their study, Yamazoe et al only included eyes with a low endothelial cell density of <1,000 cells/mm 2 with a mean ECL of 11.5 %±23.4 %.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low ECD was defined as ECD less than 1200 cells/mm 2 . 18 Corneal diseases with normal ECD (defined as 1500 cells/mm 2 or more) included 18 eyes with old corneal scars, 11 eyes with hereditary corneal epithelial/stromal dystrophies (lattice corneal dystrophy 3a, 6 eyes; macular corneal dystrophy, 3 eyes; and granular corneal dystrophy 2, 2 eyes) and 6 eyes with keratoconus. None of the eyes with keratoconus had a history of acute hydrops.…”
Section: Methodsmentioning
confidence: 99%
“…The reported endothelial loss varies between 4% and 25%, and the period of increased postoperative endothelial cell loss remains unknown. 7 Endothelial cell loss begins soon after surgery, continues for at least 10 years postoperatively and may throughout the patient's life.…”
Section: Image Analysismentioning
confidence: 99%